IMPLEMENTATION OF SERVICE EXCELLENCE IN HIGHER EDUCATION TO INCREASE STUDENT SATISFACTION AS CUSTOMERS: A CASE STUDY OF A PRIVATE UNIVERSITY IN JAKARTA - Ihin Solihin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Every educational institution must of course have quality and qualified Human Resources (HR). Not only the teaching staff or lecturers, but also need to be supported by competent staff/educational staff so that the "consumers" we serve can achieve maximum satisfaction. In the world of higher education, the consumers referred to here can be students, parents or other parties who collaborate with the university in question. However, considering that almost all activities in higher education are always related to students, the concept of excellent service must also focus on the needs of the students themselves. This research is aimed at answering the question of how excellent service is implemented at XYZ private university and whether the services from the university provide satisfaction to its students. Data collection was carried out using semi-structured interviews with 10 students who were studying in the first semester and 10 other students who had been studying for up to 6 semesters. This classification of informants was carried out to obtain an idea of whether there were differences between the services provided to new students and old students. Apart from that, to see whether there have been any changes made towards better service for students as customers. The results of this research indicate that the A6 aspect of excellent service has not been implemented properly so that it does not provide satisfaction to students who are customers or clients which is very important for the sustainability of a higher education institution.